Diversity and Distribution Patterns of Macrozoobenthos in the Intertidal Zone of Pasumpahan Island, Padang City, West Sumatra Province - Utari, Vannesa; Thamrin, Thamrin; Tanjung, Afrizal (Journal of Coastal and Ocean Sciences, 2023)
Macrozoobenthos are organisms that live sedentary (sessile) and have varying adaptability to environmental conditions. In addition, the level of diversity found in the aquatic environment can be used as an indicator of pollution. The purpose of this study was to determine the type, abundance, diversity, and distribution pattern of macrozoobenthos in the intertidal zone. This research was conducted in the waters of Pasumpahan Island. The method used in this study was a survey method, while sampling was carried out using three stations and each station consisted of 3 transects and three sub-zones using a 1m x 1m quadrant map. The results of this study found that the abundance value at each station was 4.22-5.78 ind/m2, while the abundance in the sub-zone ranged from 3.00-7.67 ind/m2, the diversity index (H') at the study sites ranged from 1.65-2.31, which means 1.0 ≤H' < 3.0 and the diversity of macrozoobenthos at the study site was categorized as moderate. The distribution pattern (Id) of macrozoobenthos at locations was clustered with a value of 1.05-1.28. The results of the One Way ANOVA test between stations obtained a value of 0.001 where p <0.05, which means H0 was rejected and there was a significant difference between the 3 stations, followed by the LSD test to find out which average between stations was the most different real